The Effect of the Antimicrobial Peptide Plectasin on the Growth Performance, Intestinal Health, and Immune Function of Yellow-Feathered Chickens - Zhang, Xinheng; Zhao, Qiqi; Wen, Lijun; Wu, Che; Yao, Ziqi; Yan, Zhuanqiang; Li, Ruoying; Chen, Liyi; Chen, Feiyang; Xie, Zi; Chen, Feng; Xie, Qingmei (Frontiers in Veterinary Science, 2021)
The goal of the study was to test the effects of an antibiotic substitute, plectasin, on the growth performance, immune function, intestinal morphology and structure, intestinal microflora, ileal mucosal layer construction and tight junctions, ileal immune-related cytokines, and blood biochemical indices of yellow-feathered chickens. A total of 1500 1-day-old yellow-feathered chicks were randomly allotted to four dietary treatments, as follows: basal diet (group A); basal diet supplemented with 10 mg enramycin/kg (group B), basal diet supplemented with 100 mg plectasin/kg (group C), and basal diet supplemented with 200 mg plectasin/kg (group D). It was found that the dietary antimicrobial peptide plectasin could increase the average daily gain (ADG) and decrease the feed to gain ratio (F/G) for the overall period of 1–63 days. Dietary plectasin can enhance H9N2 AIV and NDV antibody levels of yellow-feathered chickens at 21, 35, and 42 days of age. Dietary plectasin can enhance the intestine structure, inhibit Escherichia coli and proinflammatory cytokines in the ileum, and ameliorate the blood biochemical indices of yellow-feathered chickens at 21 days of age. This study not only indicates that the antimicrobial peptide plectasin has beneficial effects on the growth performance, intestinal health, immune function, and blood biochemical indices of yellow-feathered chickens, it also provides support for the use of plectasin as a novel feed additive for yellow-feathered chickens.